Study of Child Custody in Artificial Womb Using Artificial Intelligence and Genetic Engineering of the Parents’ Fertilized Egg - Seiwan, Anwar Nather (American Journal of Biomedicine and Pharmacy, 2025)
Artificial womb technology is an exciting and revolutionary development that could revolutionize how humans reproduce. An artificial womb could provide a solution for those unable to conceive or find a suitable surrogate mother, reducing high-risk pregnancies and premature births. Furthermore, countries with low populations could quickly leverage this technology to find solutions through laboratory-grown babies instead of natural births. Artificial intelligence is increasingly important in medicine and healthcare today, so it’s no surprise that AI will play a key role in future developments related to artificial womb technology. Using AI algorithms, such as machine learning, deep learning, and natural language processing, medical professionals can gain insights into data collected from patients. Some medical devices are being studied as new reproductive technologies that could ensure embryo implantation or support a premature baby outside the mother’s womb (whether human or animal). On this basis, it is more reliable. Based on the basic concept that every week of appropriate care outside the womb allows for significant improvements in the outcome and survival of premature babies, the "medical unit" will need to be studied and implemented in detail. For use on premature human babies, up to those born at 22 weeks of gestation, who require special assistance to ensure the development of critically immature essential organs and, consequently, normal cardiac and respiratory function, a cause of morbidity and mortality in these vulnerable patients. Scientists will develop a prototype specifically for clinical use. Unlike current incubators, the prototypes will envelop premature babies in fluid and provide them with oxygen and nutrition via an artificial placenta connected to the newborn’s umbilical cord. Genetic engineering also plays a major role in the birth process using an artificial womb, as it solves the problems of genetic deformities and mutations that may occur to the fetus in the natural womb and which cannot be modified inside the mother’s body before birth. Therefore, the artificial womb has made it possible to modify the genes of the fetus before birth, as it removes the dangerous gene that causes the mutation and repairs it so that children are born in complete health and free of diseases.